Bose–Einstein condensation of light in a semiconductor quantum well microcavity - Schofield,RC; Fu,M; Clarke,E; Farrer,I; Trapalis,A; Dhar,HS; Mukherjee,R; Severs,Millard T; Heffernan,J; Mintert,F; Nyman,RA; Oulton,RF (Nature Photonics, 2024)
When particles with integer spin accumulate at low temperature and high density, they undergo Bose–Einstein condensation (BEC). Atoms, magnons, solid-state excitons, surface plasmon polaritons and excitons coupled to light exhibit BEC, which results in high coherence due to massive occupation of the respective system’s ground state. Surprisingly, photons were shown to exhibit BEC recently in organic-dye-flled optical microcavities, which—owing to the photon’s low mass—occurs at room temperature. Here we demonstrate that photons within an inorganic semiconductor microcavity also thermalize and undergo BEC. Although semiconductor lasers are understood to operate out of thermal equilibrium, we identify a region of good thermalization in our system where we can clearly distinguish laser action from BEC. Semiconductor microcavities are a robust system for exploring the physics and applications of quantum statistical photon condensates. In practical terms, photon BECs ofer their critical behaviour at lower thresholds than lasers. Our study shows two further advantages: the lack of dark electronic states in inorganic semiconductors allows these BECs to be sustained continuously; and quantum wells ofer stronger photon–photon scattering. We measure an unoptimized interaction parameter ( g  10–3), which is large enough to access the rich physics of interactions within BECs, such as superfuid light.